Recurrent neurotoxity in Naja kaouthia envenomation: A case report from Assam, India. (15th January 2023) - Giri, Surajit; Taye, Simanta Jyoti; Shyam, Ruma; Saikia, Bandana; Jangid, Rajib; Yasmin, Rafika; Doley, Robin
Abstract: A 35 year old, male patient, bitten by Naja kaouthia with mild pain was admitted in Demow Government Community Health Centre. After 90 min post bite he developed neurotoxic symptoms. As per standard protocol, the patient was treated with 25 vials of antivenom and two doses of glycopyrrolate and neostigmine. Subsequently, he was seemingly devoid of any neurotoxic symptoms and showed signs of recovery. However, after 70 h, the neurotoxic symptoms recurred, and the patient was again treated with an additional 10 vials of ASV along with one dose of glycopyrrolate and neostigmine. Subsequently, the patient recovered completely from all the other symptoms of envenomation. This is the first report of recurrence of neurotoxic symptoms in a patient envenomed by Naja kaouthia in Assam, India and supports the need for greater attention and careful documentation of management of snakebite in the region. Graphical abstract: Image 1 Highlights: This is the first case report of recurrent neurotoxic symptoms observed in Naja kaouthia envenomation from Assam, India. The patient recovered on treatment with 25 vials of antivenom and 2 doses of neostigmine when admitted to the hospital. Neurotoxic symptoms recurred 70 h post bite and the patient was given another 10 vials antivenom and 1 dose neostigmine. The patient became stable after 30 min of second dose of antivenom and was under observation for 72 h. He was discharged after being asymptomatic on the 6th day.